How do information strategy and information technology governance influence firm performance? - Wang, Fanlin; Lv, Jianing; Zhao, Xiaoyang (Frontiers in Psychology, 2022)
Organizations today engage in turbulent competitive to seize opportunities and cope with challenges by making strategy planning, increasing information technology (IT) investment and other means. This study extends existing research on information strategy and IT governance by exploring the synergistic effects of information strategy and IT governance on firm performance. The empirical analyses are based on survey data by questionnaires, on-site interviews and other methods. The results show that: firstly, IT governance and information strategy as explanatory variables have significant influence on firm performance. Secondly, IT governance has positive effect on the relationship of information strategy and firm performance, which is a significant conclusion on the relationship between IT governance and information strategy. The conclusion provides management insight and practical guidance for enterprises to transform from the inherent pattern of traditional governance into the new technology governance, actively implement information strategy to improve firm performance.